Integrasi Budaya Pesantren dalam Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah - Jalaludin Faruk Azhari; Raudlatul Jannah (Institut Agama Islam Hidayatullah Batam, 2025)
The purpose of this study is to examine how Arabic language instruction at MI At-Tahririyah Bangkalan incorporates Islamic boarding school culture. The research uses a qualitative approach with the type of field research. Data collection techniques include participant observation, interviews and doument. The findings demonstrated how MI At-Tahririyah combined the Islamic boarding school curriculum with the Merdeka Curriculum using three strategies: developing teaching materials based on Islamic boarding school values, learning grammar with a contextualization of Islamic boarding school life, and learning vocabulary based on the Islamic boarding school context. MI teachers and female teachers from Islamic boarding schools worked together to construct the module In the cultural setting of Madurese Islamic boarding schools.